Inflammation and Circulating Natriuretic Peptide Levels. (July 2020) - Fish-Trotter, Hannah; Ferguson, Jane F.; Patel, Nirav; Arora, Pankaj; Allen, Norrina B.; Bachmann, Katherine N.; Daniels, Lori B.; Reilly, Muredach P.; Lima, Joao A.C.; Wang, Thomas J.; Gupta, Deepak K.
Abstract : Background: NPs (natriuretic peptides) are cardiac-derived hormones that promote natriuresis, diuresis, and vasodilation. Preclinical evidence suggests that nonhemodynamic triggers for NP release exist, with a few studies implicating inflammatory stimuli. We examined the association between inflammation and NP levels in humans. Methods: The associations between inflammation and NP levels were examined in 3 independent studies. First, in 5481 MESA (Multi-Ethnic Study of Atherosclerosis) participants, the cross-sectional (exam 1) and longitudinal (exams 1 to 3) associations between circulating IL6 (interleukin-6) and NT-proBNP (N terminal pro B-type natriuretic peptide) levels were examined in multivariable-adjusted models. Second, in a prospective study of 115 healthy individuals, changes in NP levels were quantified following exposure to lipopolysaccharide as an inflammatory stimulus. Third, in 13 435 hospitalized patients, the association between acute inflammatory conditions and circulating NP levels was assessed using multivariable-adjusted models. Results: At the baseline MESA exam, each 1-unit higher natural log IL6 was associated with 16% higher NT-proBNP level ([95% CI, 10%–22%]; P =0.002). Each 1-unit higher baseline natural log IL6 level also associated with 6% higher NT-proBNP level ([95% CI, 1%–11%]; P =0.02) at 4-year follow-up. In the lipopolysaccharide study, median NT-proBNP levels rose from 21 pg/mL pre-lipopolysaccharide to 54 pg/mL post-lipopolysaccharide, P <0.001. In the hospitalized patient study, acute inflammatory conditions were associated with 36% higher NP levels ([95% CI, 17%–60%]; P <0.001). Conclusions: Inflammation appears to be associated with NP release. Interpretation of NP levels should therefore take into account inflammatory conditions. Abstract : Supplemental Digital Content is available in the text.